Pregnancy of Unknown Location: The Value of Frozen Section Analysis and Its Relation to Beta-hCG Levels and Endometrial Thickness - Odeh, Marwan; Qasoum, Ayat; Tendler, Rene; Kais, Mohamad; Khamise Farah, Rola; Bornstein, Jacob (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective Frozen section examination is a rapid method for identifying products of conception in endometrial curetting, yet its accuracy is inconclusive. The purposes of this study is to determine the accuracy of frozen section analysis of endometrial curetting in pregnancies of unknown location, and to verify the relation of β-human chorionic gonadotrophin (hCG) level and endometrial thickness to the assessed accuracy.Methods We reviewed data from January 2009 to December 2014 of diagnostic curettages from women with suspected ectopic pregnancies sent for frozen section examination at a medical center. A frozen section diagnosis was considered accurate if it concurred with the final pathologic diagnosis.Results Of 106 frozen section studies, the diagnosis was accurate in 94 (88.7%). Of 79 specimens interpreted as negative on frozen sections (no products of conception noted), 9 (11.4%) were positive on final pathologic review. Three of the 27 (11.1%) specimens interpreted as positive by a frozen section failed to demonstrate products of conception on a final pathologic section. The sensitivity of frozen sections in the diagnosis of ectopic pregnancy was 72.7%, specificity 95.9%, positive predictive value 88.9%, negative predictive value 88.6%, and accuracy 88.6%. A statically significant correlation was found between β-hCG level and high accuracy of the frozen section technique (p < 0.001). No correlation was found between endometrial thickness and the accuracy of the frozen section technique.Conclusion The accuracy of frozen section examination was high and was found to correlate with β-hCG level, but not with endometrial thickness.
Keywords: ectopic pregnancy; frozen section; pregnancy of unknown location; β-hCG; endometrial thickness